Os projetos xakriabá a partir dos recursos públicos para o fomento à cultura - Terezinha Maria Furiati de Oliveira (2014)
This research aims to analyze the participation of the indigenous people Xakriabá in the Government policy to promote and encourage culture proposed by the Ministry of Culture from its restructuring in 2003 and the forms of appropriation and management of this policy adopted by that people. Participation processes by the Xakriabá were analyzed in the edicts of Fundo Estadual de Cultura (2008), Ponto de Cultura (2008) and in the Prêmios das Culturas Indígenas (2006 to 2012). The analysis of the processes triggered by the implementation of the projects had as a reference, on the one hand, the proposal of survey, revitalization and promotion of xakriabá "culture", as affirmed by the Xakriabá, and on the other, the citizen, symbolic and economic dimensions of culture with which operates the Ministry of Culture. We seek to understand the management of projects financed by the area of culture, and the tools incorporated by the Xakriabá to adapt their proposals to the requirements of the laws of promotion and incentive to culture. For the Xakriabá the idea of "culture" is something wider, which confronts the compartmentalized view of public policy. The cultural management of xakriabá projects reveals that there is no policy to promote culture directed towards indigenous peoples.